High-pressure Melting Curves of and Phases of Iron - Hong, Nguyen Thi; Khac Hieu, Ho (VNU Journal of Science: Mathematics - Physics; Vol 35 No 4, 2019)
In this study, statistical moment method (SMM) was applied in combination with Lindemann melting criterion to investigate pressure effects on melting temperature of iron. Melting curves of  phase with body-centered cubicstructure and phase with face-centered cubicstructure of iron were derived up to pressure 13 GPa and 90 GPa, respectively. The study results show that melting curves of these two phases of iron increased functions of pressure, and the higher the pressure was the lower the slopes of melting curves were. The results were compared with the available experimental data to verify the developed theory. The efficiency of the SMM on the investigation of melting temperatures of  and phases of iron suggests that the present SMM scheme can be developed extensively to determine melting temperatures of other phases of iron as well as other materials.